Cortical activation and functional connectivity during different attention tasks using functional near-infrared spectroscopy in middle-aged and elderly people - Lijuan Ding; Yiru Zhang; Youshu Xie; Yongzhi He; Yunyun Wang; Jiachun Lu; Rizhao Pang; Wenchun Wang; Zhesi Chen (European Journal of Medical Research)
Abstract Background Attention plays a vital part in the cognitive process, where different kinds of attention are associated with separate brain mechanisms. The objective of this research was to investigate the patterns of brain activation and functional connectivity in middle-aged and elderly individuals, while they were engaged in various attentional tasks, with the intention of establishing a reference foundation for the clinical treatment of attention disorders. Materials and methods A total of 44 healthy middle-aged and elderly persons (47.1% women) aged over 40 were enrolled in this study. The digital cancellation test (DCT), the paced auditory serial addition test (PASAT), the Stroop colour-word test, and the trail making test (TMT) are, respectively, associated with four types of attention tasks: sustained attention, divided attention, selective attention, and attention shifting. Functional near-infrared spectroscopic imaging was employed to measure the concentration of brain oxyhaemoglobin in the subjects, while they were performing these four attention tasks. Results In this study, we found distinct activation patterns in brain areas, such as BA-3, BA-4, BA-6, and others. Functional connectivity analysis revealed that the frontal and right parietal lobes consistently showed higher density and strength of connections across tasks, with the PASAT task exhibiting the highest number of connections exceeding the threshold. Notably, the DCT task demonstrated significant correlations in oxygen fluctuations among several brain regions, while the TMT-B task highlighted strong functional connectivity within the bilateral frontal and parietal lobes. Conclusions This research provides evidence that middle-aged and elderly people have different brain activation and functional connectivity patterns in different attentional tasks, suggesting individualized treatment for attention disorder patients based on impairment type and location. Trial registration: This study has been registered through the Chinese Clinical Trial Registry (ChiCTR2400087755).